Rituximab in the Management of Autoimmune Bullous Diseases: A Treatment-Resistant Case Series from a Single Central European Referral Center - Maciej Marek Spałek; Magdalena Jałowska; Monika Bowszyc-Dmochowska; Marian Dmochowski (Medicina, 2024)
Background and Objectives: Rituximab (RTX) has been the predominant treatment for autoimmune bullous diseases (AIBDs). The objective of this research was to assess the advantages and safety characteristics of RTX treatment in individuals with AIBD. This assessment focused on clinical remission and a reduction in glucocorticosteroid usage, its effect on the titers of autoantibodies targeting desmoglein-1 (DSG-1) and desmoglein-3 (DSG-3), and adverse occurrences during a 12-month follow-up period in a dermatology department within a Central European university context. Materials and Methods: Our case series involved eleven patients, including eight patients with pemphigus vulgaris, two with pemphigus foliaceus, and one with epidermolysis bullosa acquisita. They received a 1 g dose of rituximab, repeated over a two-week interval. Results: The reduction in a prednisone-equivalent dosage after 2, 6, and 12 months following the second RTX infusion was 65.05%, 73.99%, and 76.93%, in that order. The titers of antibodies against DSG-1 exhibited reductions of 43.29%, 75.86%, and 54.02% at 2, 6, and 12 months, respectively. By contrast, the antibody concentrations targeting DSG-3 displayed a decrease of 27.88%, 14.48%, and 5.09% at the corresponding time points. Over the course of the 12-month monitoring period, 18.18% of patients experienced disease relapse, while the remaining individuals achieved either complete or partial remission with minimal or no therapy. Adverse effects were noted in 36.36% of the patient population; they were mild, and no serious adverse effects were reported. Conclusions: RTX represents an efficacious and well-tolerated therapeutic option for the management of AIBD and merits consideration in cases of refractory AIBD. However, further research is imperative to delineate the most optimal dosage, dosing frequency, and total quantity of maintenance infusions required. Additionally, there is a compelling need for studies that explore the impact of RTX on individuals with AIBD who do not exhibit a significant reduction in anti-desmoglein autoantibody levels.